Perkembangan industri minyak dan gas Sabah (1881-1980): Penelitian terhadap eksplorasi di Laut China Selatan - Amy Azuan Abdullah; Yew, Meng Lai (Penerbit USM, 2022)
This study focuses on oil and gas exploration in the South China Sea (SCS) from the period of the British North Borneo Company’s (BNBC) administration of North Borneo in 1881 until the introduction of the National Cabotage Policy (Malaysia) on 1st January 1980. The interesting history of Sabah’s oil and gas exploration needs to be revisited especially following the establishment of Petroliam Nasional Berhad or Petronas in 1974 which has enabled Sabah to be supplied with oil and gas resources produced from the offshore wells in 1980. This analysis relies heavily on primary sources in the form of official documents, reports and newspapers obtained from the Sabah State Archives (SSA), Malaysia. The study found that, although oil exploration of North Borneo or Sabah was initially carried out by BNBC since 1881, it was only strengthened after the end of the Japanese occupation. This development became more pronounced following the changes in the rule-based international system, notably the introduction of maritime law starting from the 1950s, which provided opportunities to both the British and Sabah governments through various companies, to conduct offshore oil exploration in the SCS. Oil exploration activities in the SCS area have proven to be lucrative, especially in terms of its contribution to the Malaysian economy.